1998
DOI: 10.1046/j.1365-2958.1998.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

FtsK is a bifunctional protein involved in cell division and chromosome localization in Escherichia coli

Abstract: SummaryThe behaviour of Escherichia coli cells in which all or part of the ftsK gene is under inducible control shows that FtsK protein has two functional domains: an N-terminal part that is required for cell division, and a C-terminal part that is involved in chromosome localization within the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(160 citation statements)
references
References 15 publications
(28 reference statements)
7
148
0
1
Order By: Relevance
“…In the ⌬rtp ⌬spoIIIE mutant, RipX would, therefore, be less effective at dimer resolution. The carboxyl-terminal domain of E. coli FtsK is homologous to SpoIIIE (30) and is required for efficient chromosome dimer resolution via dif recombination (26)(27)(28)(29). Like SpoIIIE, FtsK localizes to the division septum (64).…”
Section: The Absence Of Rtp Probably Results In An Increase In Chromomentioning
confidence: 99%
“…In the ⌬rtp ⌬spoIIIE mutant, RipX would, therefore, be less effective at dimer resolution. The carboxyl-terminal domain of E. coli FtsK is homologous to SpoIIIE (30) and is required for efficient chromosome dimer resolution via dif recombination (26)(27)(28)(29). Like SpoIIIE, FtsK localizes to the division septum (64).…”
Section: The Absence Of Rtp Probably Results In An Increase In Chromomentioning
confidence: 99%
“…In addition, six so-called par genes involved in decatenation of interlinked daughter chromosomes have been characterized, as well as a number of genes thought to be involved in chromosome movement and partitioning (reviewed in reference 43). Among the latter group are the muk, minD, and ftsK genes of E. coli (12,23,49) and the smc, spoOJ, and spoIIIE genes of B. subtilis (6,13,26,45). Finally, recent work by Lemon and Grossman (19) indicates that the process of DNA replication itself may contribute to the movement and separation of daughter chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, PrfA has no significant primary sequence homology to known recombinases, indicating that the effect of PrfA on homologous recombination may be indirect. Interestingly, the C-terminal domain of the E. coli FtsK protein, which is involved in chromosome segregation (23,49), was recently shown to be required for resolution of chromosome dimers by site-specific recombination at dif, and it was suggested that FtsK could play a general role in preparing the nucleoid structure in a way that allows dif and the XerC/D recombinases to function properly (40). A XerC and XerD homologue, RipX, was recently identified in B. subtilis, and it was shown that ripX cells display chromosome segregation defects similar to those reported here for prfA cells (36).…”
Section: Vol 182 2000mentioning
confidence: 99%
“…The N-terminus is responsible for targeting FtsK to the division machinery, where it plays an essential role in the septation process Yu et al, 1998]. The Cterminus, by contrast, is dispensable for divisiome function and acts as an ATP-dependent DNA translocase [Aussel et al, 2002;Saleh et al, 2004] that pumps DNA away from the septal region of the cells [Liu et al, 1998;Yu et al, 1998]. It is still unclear how FtsK determines the direction its substrate has to be translocated to be positioned in the correct daughter cell compartment.…”
Section: The Last Stages Of Dna Replicationmentioning
confidence: 99%